TFP estimation and productivity drivers in the European Union - Agnieszka Gehringer; Inmaculada Martínez-Zarzoso; Felicitas Nowak-Lehmann Danzinger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper examines the development and drivers of total factor productivity (TFP) in the manufacturing sector for a panel of 17 EU countries over the period of 1995-2007. Recent panel data estimation techniques are used in a twofold approach. First, we estimate aggregated and sectoral TFP for 17 EU countries by means of the augmented mean group estimator to control for endogeneity, cross-section dependence and heterogeneous production technology. Second, we investigate the relative importance of the drivers of predicted TFP, namely Foreign Direct Investment (FDI), investment in Information and Communication Technologies (ICT), human capital, R&D, trade openness and rationalization efforts. The results confirm that rationalization, human capital and ICT are the main drivers of TFP.
Keywords: C26; F43; O47; 330; sectoral TFP; heterogeneous production functions; common dynamic process; European Union